PP447 Informing The Development And Evaluation Of An Evidence-Based Service Delivery Model For Mental Health Patients With Complex Needs. (December 2021) - Saini, Pooja; Martin, Antony; McIntyre, Jason C.; Sambrook, Laura; Roks, Hana; Burton, Sam; Balmer, Anna; Shetty, Amrith; Nathan, Rajan
Abstract : Introduction: Mental health services for adults have been developed to provide community-based interventions. There is a recognized unmet need in some of the most complex patients that may not be adequately met by existing mental health services provision. Research is warranted to consider the best model of service delivery for this group of service users. The aims of this research were to examine the profile and history of service users defined as having complex needs as well as their service use and associated costs in the Cheshire and Wirral Partnership NHS Foundation Trust (CWP). Methods: A diverse group of stakeholders were invited to provide feedback on the content and design of the proforma for data collection from the medical records of service users. The rationale of the data collection was described to ensure relevant patient-level cost information was collected to identify and quantify the relevant resources consumed, to inform the evaluation of direct medical costs, direct non-medical costs, and indirect costs for each patient. The proforma was designed to also permit comparisons of clinical and service use outcomes for evaluation of patient health and non-health outcomes associated with alternative care pathways. Results: Stakeholder feedback comprised representatives from the CWP, patients, commissioners, the Local Authority, and housing. Relevant data for extraction from patient medical records were identified and a proforma was developed. The following items were identified for inclusion: baseline demographic data, service user data (family background, contact with the criminal justice system, social history), and clinical data (diagnosis, treatment, hospital visits, and other health service use). Conclusions: A proforma was developed with diverse stakeholder involvement to inform data collection on the resource use and cost impact associated with alternative care pathways in the National Health Service and other sectors of the economy. Based on the proforma developed and data extracted, an exploration of patient health and non-health outcomes associated with alternative care pathways will be conducted to inform service evaluation and to promote patient centric care.